Paul Verlaine : A Bilingual Selection of His Verse - Verlaine, Paul, 1844-1896 (Book collections on Project MUSE., 2021)
Crowned "Prince of Poets" in his later years, Paul Verlaine stands out among the iconoclastic founders of French modernist verse. This diglot anthology offers the most comprehensive selection of Verlaine's poetry available in English translation. Verlaine's famous works are presented here alongside poems never previously translated into English, including neglected political works and prison pieces only recently brought to light, which reveal social, homoerotic, and even pornographic inspirations. The poems are organized not by collections and date of publication but by themes and time of composition. This innovation, along with Valazza's extensive supporting materials, will help the curious student or scholar explore the master poet's work in the context of his troubled life: from the beginning of his literary career among the Parnassians to his affair with Rimbaud and the end of his marriage, his time in prison, and his bohemian lifestyle up to his death in 1896. Verlaine, the poet of ambiguity, has always been a challenge to translate. Rosenberg expertly crafts language that privileges the musicality of Verlaine's verse while respecting each poem's meaning and pace. Featuring 192 poems in French with English translations, this collection will appeal to scholars and poetry enthusiasts alike.